Robotic and sensor technology for frozen shoulder Rehabilitation (Journal of Pharmaceutical Negative Results, 2022)
A common clinical shoulder problem is frozen shoulder. The degree of shoulder joint movement must be measured as part of the rehabilitation procedure. These assessments can be used to assess the severity of a patient's disease, set rehabilitation goals, and determine the appropriate level of activity difficulty, as well as comprehend the rehabilitation's impacts. In the healthcare industry, robots are rapidly being used; as they are in many other industries, Specifically for hospital logistics support, surgery, and rehabilitation. Because rehabilitation affects millions of individuals all around the world, there has been steady growth in the rehabilitation robotics sector over the last decade, with the advent of new technology aimed at overcoming the different challenges that this industry faces. A model is proposed in this study for identifying movements produced during frozen shoulder rehabilitation activities. The model is made up of wearable wireless sensor network (WSN) inertial sensor nodes that were built particularly for this investigation and enable for the identification of inertial sensor nodes of physiological movements anywhere. We describe current robotic systems for shoulder rehabilitation in this work, with an emphasis on indicators and further emerging technologies that, when used with robots, can enhance the advantages of rehabilitation for regaining shoulder function.